Meningkatkan Kemampuan Berbicara Bahasa Inggris Siswa pada Materi Describing People dengan Menggunakan Media Spinning Wheels di Kelas VII SMPN 2 Kasui - Wijaya, Mike (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
The study aimed at improving students' English speaking skills especially on the material of Describing People by using spinning wheel media. The sample of the study were the students of SMPN 2 Kasui grade 7B in the which consists of 8 male students and 11 female students. Can the use of spinning wheel media improve students' English-speaking skills in describing people material? This research used classroom action research which consists of two cycles. data were obtained through speaking assessment sheets, observation sheets and interview with the students. The result of the research showed the increase of students' English-speaking skills by 18.68 points at the end of cycle II. By looking at the observation sheet and the results of speaking assessments sheets in cycle II, it can be concluded that the use of spinning wheel media, besides able to increase student’s activity in the classroom, it can also improve students' English-speaking skills, especially in the material of Describing People.